THE ELIZABETHAN ANTI-STAGE MOVEMENT - Lie, Anita (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Criticism of the theater in the Elizabethan period was not the first thing happened in the history of the world’s drama. Most historians and critics agree that the antitheatrical prejudice began with Plato. The Platonic belief in the reality of the Idea was often referred to in later arguments against the stage. According to Plato, the physical world is not real because it is an imitation of the Idea and only the Idea is the Truth. Thus, art is three times removed from the Truth because it is an imitation of the physical world. In the Elizabethan era, the anti-stage arguments were later intensified with the conflict of power among the Church, the City and the Court.